STRENGTHENING OF RC BEAMS WITH EXTERNALLY BONDED AND ANCHORED FRP LAMINATE - Cameron, Ryne (My University, 2012)
Premature debonding of externally bonded FRP laminate from retrofitted reinforced concrete (RC) members can lead to inefficient use of FRP and can limit the level of strength increase that can be achieved. In this investigation, novel carbon FRP anchors were used in an attempt to delay the onset of premature debonding and to achieve superior strength. Nine double shear tests were performed on small scale concrete prisms to determine the most suitable epoxy for bonding the anchors to the laminate and the concrete. One type of epoxy increased the ultimate load of the prism retrofitted with two anchors at each end of the laminate 83.7% over the control specimens without anchors. The second phase of the investigation consisted of testing six large scale T-beams with a 4500 mm span, 400 mm height and 500 mm flange width under four point bending. Two beams were tested without FRP reinforcement as control beams, one beam was tested with FRP only epoxy bonded and the remaining three beams were tested with the FRP epoxy bonded and anchored. One of the beams with 30 anchors exhibited a 46% increase in the debonding load over the beam without anchors while the FRP laminate attained a maximum strain equal to 80% of its ultimate strain capacity, a 94% increase over the beam strengthened with only epoxy bonded FRP. The results demonstrate the anchoring system’s effectiveness and a feasible way to efficiently utilize the FRP laminate.
Keywords: FRP; debonding; external reinforcement; anchors; concrete; Civil Engineering; Construction Engineering and Management; Structural Engineering; Civil Engineering